Angiotensin converting enzyme inhibitors versus receptor blockers in patients with ventricular tachyarrhythmias - Schupp, Tobias; Behnes, Michael; Abumayyaleh, Mohammad S. A.; Weidner, Kathrin; Mashayekhi, Kambis; Bertsch, Thomas; Akın, Ibrahim (Journal of Clinical Medicine, 2022)
Data investigating the prognostic value of treatment with angiotensin converting enzyme inhibitors (ACEi) and receptor blockers (ARB) usually focusses on patients presenting with heart failure (HF) or acute myocardial infarction (AMI). However, by preventing adverse cardiac remodeling, ACEi/ARB may also decrease the risk of ventricular tachyarrhythmias and sudden cardiac death (SCD). Although ventricular tachyarrhythmias are associated with significant mortality and morbidity, only limited data are available focusing on the prognostic role of ACEi/ARB, when prescribed for secondary prevention of SCD. Therefore, this study comprehensively investigates the role of ACEi versus ARB in patients with ventricular tachyarrhythmias. A large retrospective registry was used including consecutive patients with episodes of ventricular tachycardia (VT) or fibrillation (VF) from 2002 to 2015. The primary prognostic outcome was all-cause mortality at three years, secondary endpoints comprised a composite arrhythmic endpoint (i.e., recurrences of ventricular tachyarrhythmias, ICD therapies and sudden cardiac death) and cardiac rehospitalization. A total of 1236 patients were included (15% treated with ARB and 85% with ACEi) and followed for a median of 4.0 years. At three years, ACEi and ARB were associated with comparable long-term mortality (20% vs. 17%; log rank p = 0.287; HR = 0.965; 95% CI 0.689-1.351; p = 0.835) and comparable risk of the composite arrhythmic endpoint (HR = 1.227; 95% CI 0.841-1.790; p = 0.288). In contrast, ACEi was associated with a decreased risk of cardiac rehospitalization at three years (HR = 0.690; 95% CI 0.490-0.971; p = 0.033). Within the propensity score matched cohort (i.e., 158 patients with ACEi and ARB), ACEi and ARB were associated with comparable long-term outcomes at three years. In conclusion, ACEi and ARB are associated with comparable risk of long-term outcomes in patients presenting with ventricular tachyarrhythmias.
Gesehen am 30.04.2024